Linking consumer trust perception in constructing an e-commerce trust model - Che Hussin, Ab. Razak; Othman, Nur Zailan; Mohamed Dahlan, Halina (Penerbit UTM Press, 2008)
Trust issues is still considered as a main obstacle in the implementation of eCommerce Due to the increasing numbers of cyber crimes committed today, consumers are faced with doubt to engage in online shopping. As a safety precaution, consumers will take certain measures to protect their information by evaluating and assessing these websites trustworthiness before an actual purchase occurs. This paper describes a model that examines the elements related to online consumer behavior and to investigate this behavior towards building and increasing trust. The applicability of the model was tested in attempt to view consumers' acceptance towards the model and its component. The fmdings indicate the respondents are aware of the trust issue surrounding e-Commerce implementation as they accept and agreed with the model and its components.